Tanah Adat (customary Land)in Negeri Sembilan: A Mini Review Towards Establishing Customary Land Forensic Model - Mualimin Mochammad Sahid; Wan Abdul Fattah Wan Ismail; Lukman Abdul Mutalib; Ahmad Syukran Baharuddin; Mahmoud Mohamed Ali Mahmoud Edris; Syed Mohammad Chaedar; Muhammad Hazim Ahmad (Usuli Faqih Research Centre PLT., 2024)
Al-Qanatir: International Journal of Islamic Studies Volume: 33 No: 4 (page: 191–198)